“I didn’t mean it that way…”: Design and evaluation of an elective course on dealing with discrimination in medical communication - Schwaab, Lena; Strauß, Bernhard; Philipp, Swetlana (GMS Journal for Medical Education, 2025)
Objective: Experiences of discrimination in the context of medical care are not uncommon and have a significant impact on the health of those affected. For this reason, an elective course (28 units) on “dealing with discrimination in medical communication” was introduced at University Hospital Jena for medical students in the clinical section, which aims to improve the communicative skills of future doctors with marginalized patients. The course was tested for the first time in the winter semester 2023/24. The evaluation was used to check whether the course is suitable for expanding knowledge and skills in dealing with discrimination, as assessed by the students themselves.